La fragmentación del bosque mesófilo de montaña y patrones de uso del suelo en la región oeste de Xalapa, Veracruz, México - Williams-Linera, Guadalupe; Manson, Robert H.; Isunza Vera, Eduardo (Instituto de Ecología, A.C., 2016)
The destruction of tropical montane cloud forest in the western region of Xalapa, Veracruz, has accelerated considerably in the last few decades. This paper objective was to determine the degree and pattern of fragmentation of cloud forest in this region. Thirty-three aerial photographs, scale 1: 20 000 (INEGI, 1993), were digitized and photo-interpreted to generate maps of vegetation and land-use. Additional information on slope, slope aspect, and human settlements was incorporated in a geographical information system (GIS). In the study area (12 843 ha), nineteen fragments of undisturbed forest remain, which occupy just 10% of the region. The dominant land uses are pasture (37%), urban areas (18%), secondary vegetation (17%) and disturbed forest (17%). The few flat areas available in the region (3.2%) are occupied by urban zones and pastures, while undisturbed forest is found mostly on steep slopes, with a northern exposure, located far from human activity. Forest fragments are surrounded by pastures, disturbed forest and secondary vegetation which may produce strong edge effects and reduce the overall undisturbed forest cover by another 15-54%, depending on the size of forest fragments. Results indicate that 90% of the forest in the region has already been destroyed and what remains is in danger of disappearing. A regional development plan is required which considers the importance of cloud forests as biodiversity reservoirs and providers of key environmental services, protects existing fragments of undisturbed forest, and simultaneously promotes the ecological restoration of disturbed forest as well as the establishment of corridors connecting forest remnants.